Inter-connected AC/DC HMGS power management with 3-phase and 1-phase ILC - Syed Abdul Razzaq; Vairavasamy Jayasankar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In AC/DC hybrid micro grid system (HMGS) power converters are always tested for is performance in distribution, its ability to provide accurate power sharing, transient stability and load dynamics. The existing control methods either complex or limited to achieve optimal power flow. This paper proposes a modified decentralized droop control scheme for interlinking converter (ILC) connected to interconnected AC and DC grids. A three coordinated model is proposed where AC frequency, ILC power and DC voltage are corresponding axis. The power sharing through the ILC is dependent on the AC frequency droop and DC voltage droop which occurs due to overloading. The control scheme is designed for single and three phases ILC. The obtained results are compared with double loop control method which shows less frequency deviations, accurate power sharing. The ILC performs autonomously and transfer power bidirectional under islanded mode. The simulation is carried in MATLAB/Simulink.